Impact of plyometric training using step-up and lateral box jumps on the improvement of leg muscle power in youth school futsal athletes - Kurniawan, Risky Sandy; Fahmi, Donny Anhar; Setiyawan, Setiyawan (CV Rezki Media, 2025)
Background: Futsal is a high-intensity sport that requires leg muscle power, especially in aerial duels, anticipating the ball, and performing powerful kicks. Limited jumping ability can reduce leg muscle power and overall performance. Objectives: This study aims to test the impact of plyometric training using step-up and lateral box jumps on the improvement of leg muscle power in youth school futsal athletes. Methods: A quasi-experimental single-group pretest-posttest design was conducted with 40 male participants over a four-week plyometric training program. Leg muscle power was measured using a vertical jump test before and after the intervention. Data were analyzed using a t-test with the assistance of SPSS. Results: Both step-up and lateral box jumps significantly increased leg muscle power (p < 0.05). The step-up group showed an average increase of 4.20 cm, while the lateral box jump group showed an average increase of 3.45 cm, with no statistically significant difference (p = 0.326). Conclusions: Both training methods effectively enhance leg muscle power and can be integrated into school-based futsal training programs to improve performance.